Defending functionalism and self-reference in memory - Fernández, Jordi (Estudios de Filosofía, 2021)
In recent work, Sarah Robins, Gerardo Viera and Steven James have provided some insightful objections to the ideas offered in my book, Memory: A Self-Referential Account. In this paper, I put forward some responses to those objections. Robins challenges the idea that being a memory could be a matter of having a particular functional role within the subject’s cognitive economy. Viera challenges the idea that the content of a memory could explain some of its phenomenological properties. And James challenges the idea that our memories could be immune to error through misidentification. All three commentators are targeting, not tangential aspects of, but fundamental assumptions in the account of memory proposed in the book. For that reason, modifying some of those assumptions would amount to proposing a whole different account of memory. I hope to show, however, that such a radical move is not necessary. For there are possible responses to the objections from all three commentators which are available within the constraints of the account proposed in the book.